On the Ligand-To-Metal Charge-Transfer Photochemistry of the Copper(Ii) Complexes of Quercetin and Rutin - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Aguirre-Quintana, M; Aguirre-Quintana, M; Mendoza-Espinola, L; Mendoza-Espinola, L; Chandia-Parra, N (2011)
In contrast to the UV-photoinduced ligand photoionization of the flavonoid complexes of FeIII, redox reactions initiated in ligand-to-metal charge-transfer excited states were observed on irradiation of the quercetin (1) and rutin (2) complexes of CuII. Solutions of complexes with stoichiometries [CuIIL2] (L=quercetin, rutin) and [Cu II2Ln] (n=1, L=quercetin; n=3, L=rutin) were flash-irradiated at 351 nm. Transient spectra observed in these experiments showed the formation of radical ligands corresponding to the one-electron oxidation of L and the reduction of CuII to CuI. The radical ligands remained coordinated to the CuI centers, and the substitution reactions replacing them by solvent occurred with lifetimes ?<350 ns. These are lifetimes shorter than the known lifetimes (?>1 ms) of the quercetin and rutin radical s decay. © 2011 Verlag Helvetica Chimica Acta AG.